Anticonstriction Effect of MCA in Rats by Danggui Buxue Decoction - Guo, Ying; Zhang, Yating; Hou, Ya; Guo, Pengmei; Wang, Xiaobo; Zhang, Sanyin; Yang, Peng (Frontiers in Pharmacology, 2021)
Danggui Buxue decoction (DBD), consisting of Angelicae Sinensis Radix (ASR) and Astragali Radix (AR), is a famous prescription with the function of anti-vasoconstriction. This study intends to probe its mechanisms on the relaxation of middle cerebral artery (MCA). Vascular tension of rats MCA were measured using DMT620M system. Firstly, the identical series of concentrations of DBD, ASR and AR were added into resting, KCl and U46619 pre-constricted MCA. According to the compatibility ratio, their dilatation effects were further investigated on KCl and U46619 pre-constricted vessels. Thirdly, four K+ channel blockers were employed to probe the vasodilator mechanism on KCl-contracted MCA. We finally examined the effects of DBD, ASR and AR on the vascular tone of U46619-contracted MCA in the presence or absence of Ca2+. Data suggested that DBD, ASR and AR can relax KCl and U46619 pre-contracted MCA with no effects on resting vessels. The vasodilator effect of ASR was greater than DBD and AR on KCl-contracted MCA. For U46619-contracted MCA, ASR showed a stronger vasodilator effect than that of DBD and AR at low concentration, but DBD was stronger than ASR at high concentration. Amazingly, the vasodilator effect of DBD was stronger than that of AR at all concentrations on two vasoconstrictors evoked MCA. The vasodilator effect of ASR was superior to DBD at compatibility ratio on KCl-contracted MCA at low concentrations, while being inferior to DBD at high concentrations. However, DBD exceeded AR in vasodilating MCA at all concentrations. For U46619 constricted MCA, DBD, ASR and AR had almost identical vasodilation. The dilation of DBD and AR on KCl-contracted MCA was independent of K+ channel blockers. However, ASR may inhibit K+ channel opening partially through synergistic interaction with Gli and BaCl2. DBD, ASR and AR may be responsible for inhibiting [Ca2+]out, while ASR and AR can also inhibit [Ca2+]in. DBD can relax MCA with no effects on resting vessels. The mechanism may be related to ASR's inhibition of KATP and Kir channels. Meanwhile, the inhibition of [Ca2+]out by DBD, ASR and AR, as well the inhibition of [Ca2+]in by ASR and AR may contribute to dilate MCA.